2009
DOI: 10.1002/mc.20521
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor induces hypoxia‐related interleukin‐8 expression in lung adenocarcinoma cells

Abstract: Rapid growth of cancer cells often creates insufficient supply of oxygen and nutrients in the tumour nest. The frequent detection of hypoxia-inducible factor (HIF) and interleukin-8 (IL-8) in afflicted tissues suggests that IL-8 expression could be associated with elevated levels of HIF. Recently, we found that hypoxia also upregulated the expression of hepatocyte growth factor (HGF) in lung adenocarcinoma (LAD) cells. However, the relationship between HGF and IL-8 has not been investigated in LAD cells. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 39 publications
6
16
1
Order By: Relevance
“…However, using in situ hybridization could adequately locate the HPV infection in UCC, not in the neighboring tissues (6). Moreover, our results indicate that HPV infection correlated with ATAD3A levels as well as those of c-MET, IL-8 and Ki-67 as well as with FIGO stages, lymph node involvement and patients' survival, which corresponded well with our prior studies that expression of these genes might be orchestrated with one another to form a malicious cycle in favor of cancer progression (6,26,27). It is worth noting that, Chinese UCC patients had a higher tendency of overexpressing ATAD3A than the American patients.…”
Section: Discussionsupporting
confidence: 89%
“…However, using in situ hybridization could adequately locate the HPV infection in UCC, not in the neighboring tissues (6). Moreover, our results indicate that HPV infection correlated with ATAD3A levels as well as those of c-MET, IL-8 and Ki-67 as well as with FIGO stages, lymph node involvement and patients' survival, which corresponded well with our prior studies that expression of these genes might be orchestrated with one another to form a malicious cycle in favor of cancer progression (6,26,27). It is worth noting that, Chinese UCC patients had a higher tendency of overexpressing ATAD3A than the American patients.…”
Section: Discussionsupporting
confidence: 89%
“…5B). The results are consistent with our in vitro data that nicotine reduced AIF expression (26,33).…”
Section: In Vivo Expression Level Of Aif Is Comparatively Low In Thesupporting
confidence: 93%
“…Recently, by confocal immunofluorescence microscopy we found that HGF, which was frequently detected in smoker patients, was expressed on surface of cancer cells (33). Therefore, the overexpressed HGF could only interact with nearby cells.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] ELISA IL-8 release in cell culture media was quantified by human IL-8/NAP-1 enzyme-linked immunosorbent assay (Bender Medsystems Vienna, Austria). [32][33][34] Spent medium from NCTC cell cultures was incubated in 96-well plates coated with anti-human IL-8. After washing of unbound IL-8, wells were incubated with biotin-conjugated anti-IL-8/NAP-1 antibody.…”
Section: Patient Treatment and Immunohistochemistrymentioning
confidence: 99%
“…Total RNA (1 mg) was reverse transcribed and progressive dilutions (1/ 10, 1/100, 1/1000) were then subjected to PCR amplification. cDNA of IL-8 was amplified using the primers previously described by Chiang 34 and by a new set of primers developed by us that were more efficient. Thus, primers used were AGCCAGGAAGAAACCACCGGA and TCCACAACCCTCTG CACCCAGT that generated an expected PCR product of 315 bp (NM000584 Genbank locus, GI:28610153).…”
Section: Patient Treatment and Immunohistochemistrymentioning
confidence: 99%